PENGETAHUAN TRADISIONAL DAN PEMANFAATAN TUMBUHAN OLEH MASYARAKAT LOKAL PULAU WAWONII SULAWESI TENGGARA - Rahayu, Mulyati; Rugayah, Rugayah (BERITA BIOLOGI, 2007)
Wawonii is one of the small islands located at S.E. Celebes. Plant Diversity and its utilization by the local people have not been recorded yet.Ethnobotanic study has been conducted in several location (Lansilowo, Wawolaa, Lampeapi and Boboloi Districts) visited in 2003-2005, using semi structural interviews and open-ended method. The result of trie study showed that community of this island consist of several ethnics (Bajo, Menui, Muna, Buton, Tolaki. Kolesusu, Jawa and Wawonii).Wawonii is the origin and majority ethnic in this island. About 200 species of plant have been used for their daily need such as for food, utensil, medicine and cosmetic, waving, energy and others.Indigenous knowledge of the local people about the species plant utilization will be discussed.